Composite Material Mechanical Characteristics Analysis by Non-Linear Regression and Error-Analysis Using Co-relation Matrix for Experimented Data - Sanjay D. Nikhade, Ravindra K. Garmode, Vivek R. Gaval, Sachin G. Solanke, (Design Engineering, 2021)
The prospective product development process is regarded as a crucial competitive component in several marketplaces. The selection of a suitable material is a critical step in the design and development of new goods. Because several factors from many dimensions must be considered, material selection is regarded as an essential non-linear statistical challenge in engineering. Improper material selection may have a detrimental impact on a company's performance. The experimented dataset for epoxy-based cotton and glass fiber reinforced composite were considered to carry out the following research. Mechanical test properties like tensile, impact, hardness and flexural were undertaken for non-linear and error analysis integrated with co-relation convolution matrix creation. The proposed method can examine the criteria or attribute in materials selection to great detail by analyzing how well various parameters fit together for building co-relation matrix, variance dependability on co-efficient analysis and selection criteria to achieve the goal for the given design problem.